Quality of life of an elite group of the military police in Anápolis - Goiás - Mendonça Siqueira Fernandes, Luana (2022)
Objective: to evaluate the quality of life of an elite group of the military police in Anápolis - Goiás. Methods: This is a descriptive, cross-sectional study carried out with military police officers from the Specialized Policing Company (CPE) in the city of Anápolis - GO, between June and November 2020, with an instrument for collecting sociodemographic data and the Quality Assessment. of Life by the World Health Organization (WHOQOL-Bref). The mean of the WHOQOL-Bref scores for the facets and domains was calculated according to the statistical model provided by the WHOQOL Group. Results: Fifty-five police officers participated in the study, 96.4% of whom were male. The age ranged from 24 to 54 years, with a mean of 37.3 years (SD ± 7.83), with the most prevalent age group being between 30 and 39 years (41.8%), in relation to the hierarchical level the majority of the police officers were sergeants (43.6%) and regarding the work shift, 100% of the police officers worked full-time and worked 24x72-hour shifts. Police officers rated the quality of life as good (58.2%) or very good (36.4%). As for satisfaction with health, police officers claimed to be satisfied (56.4%) or very satisfied (29.1%). Quality of life scores ranged from 62.5 to 83.25. The highest score was for the Social Relations domain (79.37) and the lowest for the Environment (71.93). The facets that presented the lowest score were: Physical Environment (62.5), Sleep and Rest (62.75), Financial Resources (63) and Recreation and Leisure (63) while the facets that presented the highest score were: Mobility (90, 5), Self-esteem (83.25), Body image and appearance (83.25) and Spirituality (89.5). Conclusion: Therefore, the evaluated military police consider the quality of life good or very good and are satisfied with their health. There is, however, a compromise in the quality of life of professionals in the factors related to the Environment domain and in the Physical Environment, Sleep and Rest, Financial Resources and Recreation and Leisure facets. Descriptors: Military; Quality of life; Health promotion.